Learning strategies and causal attributions in second language learning - Sorić, Izabela (Array, 2008)
Summary: Although in itself “motivation to learn” is a complex multifaceted construct, according to Dornyei (2001), the picture becomes even more complex when the motivation to learn a foreign/second language is concerned. It seems that a better understanding of the dynamic relationship between learners’ use of language learning strategies and the causal attributions they make for their achievement in language learning is necessary in order to direct and improve learners’ motivation. The present study was an attempt to analyse some aspects of this relationship. The sample consisted of 236 primary and secondary school students who learn English as a second (foreign) language. First, the students assessed their achievement in English (the mid-term grade) either as success or failure. After that two self-report questionnaires were applied: The Strategy Inventory for Language Learning (Oxford, 1990) and The Causal Attribution Scale (Sorić, 1998). Obtained analyses showed that relationships between learning strategies and causal attributions are very complex, especially in the case of academic failure. Learning strategies were the significant predictors of the causal attributions which both successful and unsuccessful students made for their performance in second language learning. The patterns of these relationships, however, are quite different for successful and unsuccessful students